Commentary: Utilizing Community-Engaged Approaches to Investigate and Address Hmong Women’s Cancer Disparities - Shannon M. Sparks (Hmong Studies Journal, 2014)
Cancer is a growing concern for women in the Hmong community. Hmong women experience poor health outcomes for both cervical and breast cancer, largely due to low rates of screening and resultant late-stage at diagnosis. Both breast and cervical cancer screening are complicated by a multitude of social, cultural and environmental factors which influence health care decision-making and can otherwise serve to restrict access. We argue that community-engaged research, an orientation which prioritizes collaborative, equitable partnerships and community voice in identifying both problems and solutions, can be a valuable approach to helping address cancer health disparities for Hmong women. Using the Milwaukee-based “Healthy Hmong Women” project as a case example, we detail how the community-engaged approach implemented by the project partners was critical in identifying factors contributing to Hmong cancer disparities and appropriate interventions, as well as the overall acceptance and success of the project. Specifically, we discuss how this approach: (1) promoted community investment and ownership in the project; (2) facilitated the integration of local perspectives and experiences; (3) built capacity to address cancer screening disparities; (4) facilitated the creation of interventions targeting multiple ecological levels; and (5) framed the community as the foundation and driver of positive change.